Intravascular laser irradiation of blood in the treatment of fibromylagia: integrative literature review - Cristina Ferreira de Santana, Flaviani; Alencar dos Santos, Anna Carolina; Pires da Luz Padinha, Caroline; Nayara Lenz, Stephanie; Aparecida de Melo, Taisy; Korelo, Raciele Ivandra Guarda (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Low-Intensity Laser Therapy (LLLT), applied to trigger points, can be used as adjuvant therapy in the treatment of Fibromyalgia. However, in Brazil, the application of intravascular technique applied transdermally on the radial artery has been widespread as a promising modality of treatment. But as far as we know, its effects are still not fully understood in the treatment of this pathology. Objective: To investigate the scientific evidence for the use of intravascular laser blood irradiation (ILIB) in the treatment of fibromyalgia. Method: this is an integrative literature review (PROSPERO registration CRD42021236744) to identify clinical studies that demonstrate the effect of ILIB on fibromyalgia, without time or language restrictions. Searches were performed and published in 4 databases (PubMed, PeDRO, EMBASE, and Scielo), by 2 independent reviewers, using the descriptors “fibromyalgia” associated with “laser” or “low-level light therapy” or “laser irradiation” ” or “photobiomodulation” or “phototherapy” or “blood irradiation” or “modified ILIB” or “intradermal ILIB”. Results: 3,050 articles were identified. Of these, only 62 met the eligibility criteria, and 32 were duplicates. Thus, 30 studies were rich, but none of them correspond to a clinical study using ILIB in fibromyalgia. However, two secondary sources and four secondary cases were found, with low methodological rigor, but which presented positive positive results, as well as antioxidant and circulatory systemic effects. No substantiated evidence of completion of IB clinical trials in fibromyalgia was identified for their clinical substantiation.